(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Globally, 4 in 5 children do not engage in sufficient physical activity, leading to increases in related diseases. Establishing healthy physical activity habits like cycling during childhood can have immediate and long-term benefits on children’s health. To this end, Cycle for Better Health focuses on increasing cycling amongst children (6–12) in vulnerable communities. This partnership between Cities for Better Health and BYCS also seeks to bridge the gap between the health and mobility sectors, leading to greater collaboration towards shared goals and showcasing the vital role of cycling in promoting physical activity and wellbeing within the health sector, and to highlight the numerous health benefits of cycling that are often overlooked within the mobility sector. Project or Policy Description: BYCS is the global coordinating partner responsible for developing the methodology, M&E and Comms, and the programme is being implemented in Bogota, Bratislava, and Bari with local, on-the-ground partners: Mamacitas en Bici, Cyklokoalícia, and Terreno. The project is divided into three phases: developing the methodology, implementing the methodology, and disseminating the results. To increase the use of cycling amongst children in each city, the programme addresses key barriers that prevent people from accessing the benefits of this mode of transportation. This approach – known as the ‘human infrastructure of cycling’ – focuses on the building blocks of awareness, education, access, and stimulation. Specific activities were co-designed in each context to fit the local needs. The project measures increases in awareness, education, access, and stimulation, as well as increases in cycling and general physical activity using participant and parent surveys as well as individual activity logs. The results and approach will be released as a report and guide, and launched at Velo-city. The implementation will be deepened in each pilot city and expanded to new cities in 2026. Conclusion: Incorporating physical activity via cycling into daily mobility habits increases the likelihood that the behaviour will be maintained. Greater collaboration between the health and mobility sectors will increase the likelihood of this system-level shift in focus.